Knowledge, attitude and perception of orthodontic treatment among dental students - Agrawal, Riya (International Journal of Dental Research, 2017)
Introduction: Malocclusion is known to contribute overall health status, as well as affecting individualâ€™s psychosocial health.Aim: To establish knowledge, attitude and perception of orthodontics treatment among dental students of one of the dental college of M.P.Material & Method: A descriptive cross study was carried out among 300 undergraduate dental students of people dental academy Bhopal M.P. India. Each classroom of the participants were visited. Self-administered questionnaire were distributed to a 300 students. The scores were calculated, and statistical analysis were done. Categorical variables were evaluated using a Chi-square test with the level of significance ofÂ PÂ < 0.001.Â Results: About 85% of the students were aware of their dental esthetics. About 85% of females were satisfied with the attractiveness of their teeth when compared to 70% males. House surgeons had more positive attitude compared to the 1st year students.Â Conclusion:Â The dental students had good knowledge about the orthodontic treatment and had a positive attitude toward it. Females had very good knowledge, satisfaction and positive attitude compared to the males regarding dental esthetics and treatment. House surgeons were much more aware, very much satisfied and had a more positive attitude than 1st year students.